Grain yield stability of rainfed oat varieties in the High Valleys of Mexico - Carranza González, Salvador; Rene Hortelano Santa Rosa (Revista Mexicana de Ciencias Agrícolas, 2025)
The grain yield stability of 12 oat varieties was evaluated in 23 localities situated in rainfed environments of the High Valleys of Mexico. Two methodologies were used to assess grain yield stability: Eberhart and Russell parameters and AMMI analysis. The stability parameters allowed us to better discriminate the varieties through the interaction they had in the environments; these parameters showed similar results to each other, in which the Ágata variety stood out for its high yield, stability, and consistency; in second place were Turquesa and Menonita, while the Cuauhtémoc, Papigochi, and Avemex varieties were the least suitable genotypes. The results showed classifying the varieties with the highest qualities for recommendation and those that no longer have potential for commercial use.
Keywords: Avena sativa L.; genotype × environment interaction; rainfed environments; yield stability